A new species of Rhinella (Anura: Bufonidae) from Northeastern Brazil - Roberto, Igor Joventino; Brito, Lucas; Thome, Maria Tereza C. [UNESP] (Soc Brasileira Herpetologia, 2014)
We describe a new species of anuran belonging to the Rhinella crucifer species group, from a relictual Atlantic Forest fragment located at the Serra de Baturite mountain range, State of Ceara, Northeastern Brazil. The new species is characterized by narrow and elongated parotoid glands, overhanging the lateral edges of the body dorsally; a conspicuous fringe on the ventral surface of the tarsus; yellow marks on the flanks of the posterior surface of thighs and cloaca; integument of the dorsum and limbs with round warts with many keratinized black spines. Tadpoles have a kidney-shaped nostril, with a dorsal fin that begins low and rises acutely once passed by the body limits; oral disc laterally emarginated, sub-marginal papillae clumped, dark papillae in some specimens. In addition, we describe call parameters of the new species, provide information regarding its natural history, and comment on its conservation status.
Keywords: Advertisement call; Amphibian conservation; Natural history; Rhinella crucifer group; Tadpole